Mejora del registro de accidentabilidad en la ciudad de Riobamba - Inca Barahona, Jorge Alexander (2020)
According to the World Health Organization (WHO), one of the main causes of death and non-fatal injuries is traffic accidents. In Ecuador, the National Institute of Statistics and Censuses (INEC), has ranked traffic accidents as the sixth leading cause of mortality. In 2011 the decentralized autonomous governments (GAD) assumed the competence for planning and regulation of traffic, land transport and road safety within the cantonal environment. The Riobamba GAD does not have a standard accident control system. The objective of this investigation is to analyze the accident registry of the GAD Riobamba Mobility, Traffic and Transport Directorate with previous records to establish its improvements. The data collection and tabulation results allowed to identify that there are six critical accident points in the city of Riobamba, the main cause of driver distraction. Applied the prediction method, it showed that the probability of traffic accidents in the city of Riobamba is 73.8% for private vehicles and taxis, while 70.6% occur for vehicles of the bus type, light load, heavy, motorcycles and others.